Implementasi Layanan Konsultasi Bimbingan dan Konseling di SMK Negeri se-Kota Semarang - Munandar, Aris; Mugiarso, Heru (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
This research was conducted based on phenomena that occur on guidance counseling teachers in vocational high school of Semarang. Implementation of consulting services guidance and counselling at the school in the execution  not as appropriate, where there are errors in execution of consulting services that lead to individual counseling services. The purpose of this research is finding empirical evidence regarding the implementation of consultancy services in the planning, implementation, evaluation,evaluation result analysis  and follow-up phases. Type of this research is descriptive research with survey method. The entire population is guidance counseling teachers vocational high school of Semarang with 49 samples using saturated sample. This research was conducted in vocational high school of Semarang with 49 counselor subject. Data collection method using question form. Analysis technique of data using descriptive percentage analysis.  This research results indicate that implementation consulting services on the planning phase 81,2%, execution phase 66,8%, evaluation phase 74,6%, evaluation result analysis phase 75,7% and follow up phase have 80,5%, and average 71,6%. That result indicates that the implementation of consulting services in vocational high school of Semarang has a good criteria.